Nonstationary Systems: Theory and Applications Contributions to the 13th Workshop on Nonstationary Systems and Their Applications, February 3-5, 2020, Grodek nad Dunajcem, Poland - Chaari, Fakher; Leskow, Jacek; Wylomanska, Agnieszka; Zimroz, Radoslaw; Napolitano, Antonio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book offers an overview of current and recent methods for the analysis of the nonstationary processes, focusing on cyclostationary systems that are ubiquitous in various application fields. Based on the 13th Workshop on Nonstationary Systems and Their Applications, held on February 3-5, 2020, in Grodek nad Dunajcem, Poland, the book merges theoretical contributions describing new statistical and intelligent methods for analyzing nonstationary processes, and applied works showing how the proposed methods can be implemented in practice and do perform in real-world case studies. A significant part of the book is dedicated to nonstationary systems applications, with a special emphasis on those in condition monitoring. .
Time-averaged statistics-based methods for anomalous diffusive exponent estimation of fractional Brownian motion -- First-order integer valued AR processes with zero-inflated innovations -- Asymptotics of alternative interdependence measures for two-dimensional alpha-stable autoregressive model of order 1 -- How to describe the linear dependence for heavy-tailed distributed data -- Granger Causality and Cointegration During Stock Bubbles and Market Crashes -- Non-Gaussian regime-switching model in application to the commodity price description -- Foundations of the Theory of Strongly Periodically Correlated Fields over Z2 -- Component and LSM-estimation of mean and covariation functions of biperiodically correlated random signals -- The synchronous fitting of cyclo-non-stationary signals : De nition and theoretical analysis -- On the modelling of phonocardiogram signals: Laplace kernel and cyclostationarity based approaches -- On the modelling of phonocardiogram signals: Laplace kernel and cyclostationarity based approaches -- Automatic detection of rolling element bearing faults for mechanical systems with gears -- Health Monitoring of Non-stationary Structures: An electromechanical Impedance Approach Using Integrated Piezoceramic Transducers -- Rub-Impact Fault Diagnosis of a Coal Crusher machine by using Ensemble Patch Transformation and Empirical Mode Decomposition -- Fault Detection of Non-Stationary Processes Using A Modified PCA Approach -- Contribution to Health monitoring of Silicon Carbide MOSFET -- The Use of Signal Intensity Estimator for Monitoring Real World Non-Stationary Data -- Model based decision support system for the blast furnace charge of burden materials -- Optimization of the Vibrating Machines with Adjustable Frequency Characteristics -- Mathematical Modelling and Computer Simulation of Rotors Dynamics in Active Magnetic Bearings on the Example of the Power Gas Turbine Unit -- Computer Method of Determining the Yield Surface of Variable Structure of Heterogeneous Materials Based on the Statistical Evaluation of Their Elastic Characteristics -- Diagnosis Methods on the Blade of Marine Current Turbine.
Keywords: Dynamics; Nonlinear theories; Signal processing; Control engineering; Machinery; Applied Dynamical Systems; Digital and Analog Signal Processing; Control and Systems Theory; Machinery and Machine Elements; Cyclostationary waves -- Congresses; Machinery -- Monitoring -- Mathematical models -- Congresses; Stationary processes -- Congresses